2021
DOI: 10.1093/medlaw/fwab025
|View full text |Cite|
|
Sign up to set email alerts
|

Feats, Flops, and Free Lessons From NZ’s Response to the COVID-19 Pandemic

Abstract: Beginning from the first reports of COVID-19 out of China, this article provides a commentary on the actions taken by the Government of New Zealand in terms of nine themes—a national response with an elimination goal, speed, and comprehensiveness of the initial response; an evidence-based, science-led approach, prioritised on protecting lives; effective communication; leadership style which appealed to collective responsibility and attempted to de-politicise the Government’s response to the virus; flexibility … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 9 publications
(10 reference statements)
1
5
0
Order By: Relevance
“…To the extent that individuals are culturally conditioned to be concerned about the wellbeing of others, their behavior in a pandemic environment is likely to change. At the same time, even within more independent and individualistic contexts, health interventions have much to gain by emphasizing the wellbeing of others, as the case study of a highly individualistic country such as New Zealand has demonstrated ( Manning, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…To the extent that individuals are culturally conditioned to be concerned about the wellbeing of others, their behavior in a pandemic environment is likely to change. At the same time, even within more independent and individualistic contexts, health interventions have much to gain by emphasizing the wellbeing of others, as the case study of a highly individualistic country such as New Zealand has demonstrated ( Manning, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…At that time, the successful vaccination programme ensured that mortality rates did not generally exceed those of other developed countries, even though many in the community would not have built up natural immunity by means of earlier exposure to the virus. Essentially, New Zealand's remoteness delayed the spread of COVID‐19, providing an opportunity to learn from the experience of other nations and to prepare (Manning, 2021), although earlier adoption of antiviral treatments might have dampened severe disease and mortality even more.…”
Section: Covid‐19‐related Policies In Aotearoa New Zealand and Their ...mentioning
confidence: 99%
“…New Zealand's 'go hard and go early' strategy at the start of the pandemic was a response to evidence from China that the new virus was more dangerous than influenza and had a shorter incubation period (Dyer, 2021). 14 The limited intensive care capacity in the national health system to handle a pandemic of this size was also a factor in the decision (Blair et al, 2022;Manning, 2021). Additionally, there was a concern that the pre-existing inequalities between European New Zealanders and M aori and Pacific peoples in the incidence of communicable and noncommunicable diseases, access to health, and social determinants of health, would expose the latter groups to unacceptably high risk during the pandemic, unless a very stringent public health response was adopted (Blair et al, 2022).…”
Section: Covid-19-related Policies In Aotearoa New Zealand and Their ...mentioning
confidence: 99%
“…In international dispute resolution as dispute resolution can be done in two forms, namely, responsibility in terms of diplomatic/political dispute resolution (Manning, 2021). As well as disputes with adjudication mechanisms within the framework of international law (O'Connell, 2017).…”
Section: Dispute Settlement Mechanism Of the States Under Internation...mentioning
confidence: 99%